Experimental evidence-based construction of electroacupuncture for ischemic stroke: a meta-analysis and systematic review - Guo, Yaoguang; Hu, Sihan; Luo, Shiman; Tu, Lang; Tang, Yao; Zeng, Fang (Frontiers in Neurology, 2025)
ObjectiveIschemic stroke represents a leading cause of disability and mortality worldwide, necessitating effective and complementary therapeutic strategies. Electroacupuncture (EA), a modern extension of traditional acupuncture, has garnered attention for its potential neuroprotective effects in ischemic stroke rehabilitation. This meta-analysis and systematic review aim to synthesize current experimental evidence on the efficacy of EA in ischemic stroke models, focusing on neurological outcomes, infarct volumes, and underlying molecular mechanisms.MethodsA comprehensive search was performed across four databases—Cochrane Library, EMBASE, PubMed, and Web of Science—to identify relevant experimental studies that utilized electroacupuncture (EA) as a therapeutic modality for ischemic stroke in animal models. This search encompassed all literature available from the inception of each library through December 2023. Studies were rigorously screened based on predefined inclusion and exclusion criteria. Data on cerebral infarction volume, neurological deficit scores, cellular apoptosis, and molecular pathways were extracted and analyzed.ResultsEleven eligible studies involving 302 animals (151 in EA treatment groups and 151 in control groups) were included. Meta-analysis revealed that EA significantly reduced cerebral infarction volumes [MD = −15.78, 95%CI (−21.40, −10.16), p < 0.05] and TUNEL-positive cells [MD = −26.46, 95%CI (−40.40, −12.51), p < 0.05], indicating reduced apoptosis. Improvements were also noted in neurological deficit scores [MD = −0.59, 95%CI (−0.92, −0.27), p < 0.05] and modified Neurological Severity Scores (mNSS) [MD = -5.68, 95%CI (−7.41, −3.95), p < 0.05], highlighting functional recovery. While the analysis showed no significant effect on caspase-3 densities [MD = −0.39, 95%CI (−0.79, 0.02), p > 0.05], a notable increase in Bcl-2 densities suggested an anti-apoptotic mechanism [MD = −0.73, 95%CI (−1.68, 0.21), p > 0.05]. The heterogeneity of the included studies points to complex underlying mechanisms, potentially involving modulation of apoptotic pathways and cerebral blood flow.ConclusionThis meta-analysis substantiates the neuroprotective potential of EA in ischemic stroke models, primarily through apoptosis modulation and possibly through improved cerebral perfusion. These findings advocate for the integration of EA into stroke rehabilitation protocols and underscore the need for clinical trials to validate its efficacy in human subjects. Our study not only reinforces the therapeutic value of EA but also prompts further investigation into its underlying mechanisms, potentially guiding more effective stroke recovery strategies.